Masters of Learned Ignorance: Eriugena, Eckhart, Cusanus. By Donald F. Duclow - Ward, Benedicta (The journal of theological studies, 2007)
This volume gathers together essays by Professor Duclow of Gwynedd-Mercy College in this series which makes valuable material already published in various places more easily accessible. Here Professor Duclow has chosen to unite his work on three medieval philosopher–theologians, the Irishman John Scottus Eriugena (c.810–77), the German Dominican Meister Eckhart (c.1260–1327), and the canon lawyer and cardinal Nicolas of Cusa (c.1401–64), under the challenging title ‘Masters of Learned Ignorance’.